Uji Adaptasi Galur Harapan Kedelai di Lahan Podsolik Merah Kuning Kabupaten Bangka - Handara, N; Suharsono, .; Mustikarini, ED (Universitas Bangka Belitung, 2014)
The purpose of this study was to determine the productivity and adaptability of ten soybean genotypes in red-yellow podzolic soils. The experiment conducted in Balunijuk village, Merawang subdistrict, Bangka on July-October 2010. Experimental design used randomized complete block design with 10 genotypes soybean replicated three times. Tested genotypes consisted of six promising lines (KH 8, KH 9, KH 31, KH 38, KH 55, and KH 71) and 4 national varieties (Slamet, Anjasmoro, Wilis and Tanggamus) as comparison. The results indicated that there were significant differences among genotypes for character plant productivity, seed size, plant height, number of root nodules, effective number of root nodules, number of pods, number of productive branches, and sheer number of seeds. Entire promising lines tested had a larger grain size than the check varieties, and the largest grain size and the highest productivity was obtained in KH 71. Therefore, KH 71 considered more promising to be released as new varieties for red-yellow podzolic soils.